Establishment and preliminary application of PCR-RFLP genotyping method for Giardia duodenalis in goats - Xuanru Mu; Jianchao Guo; Hongcai Wang; Yilong Li; Kaijian Yuan; Hui Xu; Wenjing Zeng; Qiaoyu Li; Xingang Yu; Yang Hong (BMC Veterinary Research)
Abstract Background Giardia duodenalis (G. duodenalis) is a globally distributed zoonotic protozoan that parasitizes the small intestines of humans and various mammals, such as goats and sheep. The objective of this study was to establish a convenient, accurate, and specific method based on restriction fragment length polymorphism (RFLP) for genotyping assemblages A, B and E of G. duodenalis in goats. The β-giardin gene was amplified using primer pairs bgF1, bgR1, bgF2 and bgR2 by nested PCR. The PCR products were digested with the restriction enzymes Hinf I and Bgl I. The established PCR-RFLP method was used to detect and analyze the genetic subtypes of G. duodenalis in 130 fecal samples from goats and compared simultaneously with microscopic examination and nucleic acid sequencing for G. duodenalis. Results Genetic sequencing confirmed that the PCR-RFLP method accurately distinguished G. duodenalis assemblages A, B and E, as well as different combinations of mixed infections of these three assemblages. Among the 130 samples tested by PCR-RFLP, a total of 26 samples (20.00%) tested positive for G. duodenalis, a higher sensitivity than microscopic examination at 13.85% (18/130). Sequence alignment analysis revealed that among the 26 PCR-positive samples, two were identified as assemblage AI, while the remaining 24 were identified as assemblage E or E12. Conclusions This study established an accurate, efficient and rapid PCR-RFLP genotyping method using the bg sequence of G. duodenalis, enabling accurate identification and effective differentiation of goat-derived G. duodenalis assemblages without requiring sequencing.